Optimal Control Study for Fractional Frequency Wind Power System - Zhuoyan Song; Xifan Wang; Yufei Teng; Lianhui Ning; Yongqing Meng (2012 Asia-Pacific Power and Energy Engineering Conference, 2012)
Fractional Frequency Transmission System (FFTS), is suitable to integrate the wind farm into grid, which uses low frequency, e.g. 50/3 Hz. The AC power of fractional frequency is transferred to industrial frequency power, and sent to the power grid by cycloconverter. The paper firstly discusses the structure of the fractional frequency wind power system (FFWPS), which is combined with wind turbine generators and FFTS. In FFWPS, the multi-pole permanent magnet direct-drive synchronous generator (PMSG) wind turbine without converter produces AC power of fractional frequency, and the rotation speed of PMSG is controlled by cycloconverter. Subsequently, the design principle of FFWPS controller is demonstrated. Abiding by the principle of power optimization, the multi-machine optimal speed scheme (MOSS) is proposed, and the simulation model of FFWPS is built in PSCAD/EMTDC. The results of simulation show that, in different wind conditions, PMSG wind turbines could capture wind energy as much as possible when using MOSS, which presents a new method that a single cycloconverter could control multi wind turbines in FFWPS.